Electrospinning for skin tissue engineering and drug-eluting antimicrobial biomaterials - Keirouz, Antonios (The University of Edinburgh, 2021)
A critical challenge in the design of biomaterials for tissue engineering relies on the development of tissue-specific biomimetic scaffolds capable of replacing cell-matrix interactions required for the repair of injured tissues. Further, such biomaterials with the additional capacity to prevent bacteria contamination can resolve issues surrounding surgical prosthesis infection. Fibrous micro- and nanostructures are extensively researched in tissue engineering due to their intrinsic similarities to decellularised human tissues. Among the several fibre-forming processes, electrospinning has drawn much attention due to its ability to produce scaffolds that morphologically resemble the native extracellular matrix (ECM) of human tissues. Electrospinning is a versatile method that uses electrohydrodynamic principles to produce fibres with diameters ranging from microns to tens of nanometres. By varying the chemistry and morphology of the fibres, it is feasible to attain different physiological and mechanical responses. The wide array of raw natural and synthetic materials – including polymers and complex molecules – that can be used to electrospin fibres can resolve well-documented problems associated with the inferiority of synthetic biomaterials and the limitations of biological tissues. In this thesis, electrospinning is utilised to contribute to the engineering of advanced ECM-mimicking biomaterials. The work will focus on (1) improving the physicochemical and mechanical responses of skin substitutes and (2) preventing mesh-associated surgical site infection. The initial study of this thesis presents the design and construction of a nozzle-free electrospinning device, which is an economically viable method of scaling-up fibre production output. The equipment is then used to fabricate elastic skin-like composite nanofibres consisting of poly(vinylpyrrolidone) (PVP) and poly(glycerol sebacate) (PGS). The findings indicate that the mechanical properties of the electrospun mats could be tuned by varying the concentration of PGS and the molecular weight of PVP within the blends. Photocrosslinking the fibres prevented the rapid degradation of the composite mats due to the hydrophilic nature of PVP, making it feasible to assess the biological responses of the construct in vitro, displaying good viability and proliferation of human dermal fibroblasts. This study provides a different approach towards the development of skin substitutes, based on the fact that mechanical stimuli influence the ability of dermal cells to adapt and reconstruct the ECM at an injured site; being able to adjust the mechanics to those of different anatomical sites of the body can have a positive effect on the overall outcome of a healing wound. Synthetic biomaterials tend to present suboptimal cell growth and proliferation, with many studies linking this phenomenon to the hydrophobicity of such surfaces. This thesis continues with the development of a protocol for silk fibroin extraction from Bombyx mori cocoons, which achieved significantly increased yields of the protein in a third of the time required by the conventional molecular cut-off extraction approach. The extracted silk fibroin was then used to produce electrospun membranes consisting of poly(caprolactone) (PCL) blended with variant forms of PGS. The main aim of this work was the development of fibre mats with tuneable hydrophobicity/hydrophilicity properties, depending on the esterification degree and concentration of PGS within each composite. By altering the surface properties of the electrospun membranes, the trinary composite biomaterial presented improved fibroblast attachment behaviour and optimal growth in comparison to PCL-only fibrous mats. The study continued with the development of an ultralight-weight nanostructured bicomponent antimicrobial construct with a similar microstructure to biologic meshes, which preserved the required mechanical integrity of synthetic mesh materials. A core/shell nanofibrous structure was developed, consisting of nylon-6 in the core and chitosan/polyethylene oxide in the shell. The bicomponent fibre structure comprised a binary antimicrobial system incorporating 5-chloro-8-quinolinol in the chitosan-shell, with the sustained release of polyhexamethylene biguanide from the nylon-6 core of the fibres. The antimicrobial nanofibres were found to elicit a robust bactericidal response, in vitro, against the two most commonly occurring pathogenic bacteria in deep incisional surgical site infections; Staphylococcus aureus and Pseudomonas aeruginosa. The results of this study advocate that the bicomponent nanofibres developed can be a promising alternative to biologic meshes, employed for hernia repair today, due to similar architecture and mechanics, but at the same time capable of actively protecting the patient from subsequent mesh-associated infections, thus tackling this life-threatening postoperative complication. Overall, the work in this thesis has expanded upon the fields of skin tissue engineering and drug-eluting antimicrobial biomaterials, potentially guiding new areas of research.
Keywords: electrospinning; wound healing; antimicrobials; drug release; surgical meshes; nanofibers; skin tissue repair; skin tissue repair; hernia; postoperative mesh infection; high-throughput production of nanofibers; nanofabrication; nanocomposites; biomaterials; implants; scaffolds; high-throughput electrospinning; co-axial electrospinning; bicomponent fibers; core/shell